Company finance and the capital market : a study of the effects of firm size - Davis, Edward W.; Yeomans, K. A.; Buckland, Roger (London : Cambridge University Press, 1974)
This book is the result of an investigation of the effects of size, amongst other factors, for the financial management of firms. As such the book is necessarily selective and focuses on two distinct aspects of corporate financial management: the resorts to the new issue markets by previously unquoted firms and of different size groups.
Includes bibliographical references: p. 134-135
hza 27/08/2018
Loans
Keywords: Corporations; Stocks; Working capital; Industries